Properties, vapour-phase antimicrobial and antioxidant activities of active poly(vinyl alcohol) packaging films incorporated with clove oil. (June 2018) - Chen, Chenwei; Xu, Zhewei; Ma, Yarui; Liu, Jinliang; Zhang, Qinjun; Tang, Zhipeng; Fu, Kaijia; Yang, Fuxin; Xie, Jing
Abstract: The active poly(vinyl alcohol) (PVA) films incorporated with clove oil (CO) at level of 1%, 3%, 5%, 7% and 9% (w/w) was prepared. The effects of CO content on the structural, mechanical, gas barrier and thermal stability properties of the films were investigated. The antimicrobial and antioxidant activities in vapour phase of the films were evaluated by investigating the microbiological analyses and lipid oxidation of the packed trichiurus haumela without contacting the PVA films. The oil droplets were observed on the surface and cross-section of the films as CO increased from 3% to 9% via scanning electron microscope (SEM). It resulted in the heterogeneous film structure featuring discontinuities. Some negative impacts on the properties of the films were observed with increasing CO. Compared with pure PVA film, the tensile strength (TS) of film added with 9% CO decreased 14.13%, the elongation at break increased 26.64%, water vapor transmission rate (WVTR) reduced 54.31%, oxygen transmission rate (OTR) increased 90.77% and thermal stability was worsened slightly. The bacterial growth and lipid oxidation of the packed trichiurus haumela were inhibited by the packaging with CO-containing films. The PVA film containing 9% CO showed the best quality protective effectiveness. Its microbiological shelf-life could be extended for 2 days and 28.07% reduction of malonaldehyde was obtained on day 7 comparing with control sample, indicating the antimicrobial and antioxidant activities were effective in vapour phase. It could be a promising active packaging for potential application in the non direct contact packaging-food system to create a protective atmosphere around the packaged foodstuffs. Highlights: The active PVA films incorporated with clove oil were developed. The films were characteristic of heterogeneous structure featuring discontinuities. Some negative impacts on properties of films were caused with increasing clove oil. The films possessed antioxidant and antimicrobial activities in vapour phase. It could be a promising active material for potential food packaging application.